2008
DOI: 10.1373/clinchem.2007.097162
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Centaur TnI-Ultra Assay for Detection of Myocardial Infarction and Adverse Events in Patients Presenting With Symptoms Suggestive of Acute Coronary Syndrome

Abstract: BACKGROUND:We determined the diagnostic accuracy of the Advia Centaur TnI-Ultra assay for detecting myocardial infarction (MI) and assessing risk of adverse events in patients presenting with ischemic symptoms suggestive of acute coronary syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
80
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(93 citation statements)
references
References 20 publications
7
80
0
6
Order By: Relevance
“…35,37,38 The published 99th percentile limit for the Centaur Troponin I assay is 0.04 mg/L, whereas the corresponding value for the Elecsys Troponin T assay is 0.01 mg/L. 39,40 During the course of this study, both EDs used 0.05 mg/L as the threshold for identifying a positive test. As the goal of this study was to investigate outcomes in patients who were knowingly discharged with positive troponins, this mandated that we also use a threshold of 0.05 mg/L to identify TP patients in both troponin assays.…”
Section: Limitationsmentioning
confidence: 96%
“…35,37,38 The published 99th percentile limit for the Centaur Troponin I assay is 0.04 mg/L, whereas the corresponding value for the Elecsys Troponin T assay is 0.01 mg/L. 39,40 During the course of this study, both EDs used 0.05 mg/L as the threshold for identifying a positive test. As the goal of this study was to investigate outcomes in patients who were knowingly discharged with positive troponins, this mandated that we also use a threshold of 0.05 mg/L to identify TP patients in both troponin assays.…”
Section: Limitationsmentioning
confidence: 96%
“…For earlier detection of myocardial necrosis, high-sensitivity (hs) assays for cardiac troponin T (cTnT) have been successfully evaluated. Studies have shown that hs assays can detect cardiac troponin concentrations in serum of healthy individuals with the required imprecision (10,11 ). Guidelines recommend the use of the 99th percentile of troponin concentrations from a healthy reference population as a cutoff with a guideline-equitable imprecision of Ͻ10% (CV Ͻ10%) (4,12 ).…”
Section: © 2012 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Myocardial injury has been reported to occur in critically ill humans and animals 1, 2, 3, 4, 5, 6, 7. Several noncardiac diseases can lead to secondary myocardial injury, which accentuates the importance of monitoring cardiac function.…”
mentioning
confidence: 99%
“…cTnI contributed significantly to the prognostic power of another scoring system for dogs with severe systemic diseases, the physiologic and laboratory evaluation (APPLE) full score in those patients 38. Using immunoassays with high sensitivity for cTnI improved the sensitivity for detection of myocardial injury as compared to older generation cTnI assays 7, 39, 40, 41…”
mentioning
confidence: 99%